Imaging features of intracranial meningiomas with histopathological correlation: a case report and review of literature - Montvilaitė , R.; Letautienė , S. R.; Kvaščevičius , R.; Barkauskienė , A. (Neurologijos seminarai, 2020)
Meningiomas are the most common non-glial tumours of the central nervous system. Most meningiomas are benign; however, 20% are associated with less favourable clinical outcomes and are considered malignant. It is important for the radiologist to distinguish between the benign and malignant features of meningiomas as they have different management strategies. Although the value of medical imaging (computed tomography, magnetic resonance imaging) in predicting the histopathologic grades of meningiomas is limited, certain features increase the probability of the lesion being malignant. In this article, we present a case report of a recurrent malignant intracranial meningioma and a literature review and analyze the correlations of the radiological characteristics of meningiomas with histopathological tumor differentiation.